2000
DOI: 10.1097/00006565-200010000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with 2-octylcyanoacrylate in a pediatric emergency department

Abstract: Octylcyanoacrylate adhesives performed well in the daily practice of a pediatric emergency department, and were used for a significant percentage of laceration closures. Convenience, average infection rates, and good parental satisfaction make tissue adhesives a valuable addition to our wound closure techniques. Certain pitfalls occurring during early experience with these adhesives can be recognized and avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Lowe (41) noticed that one of the most important predictors of parental satisfaction in pediatric laceration repair is "provider performance, " comprising communication, attitude, hygiene and confidence of the physician. Many studies naturally address the parental point of view, (41,42) as self-reports are limited by age, but thus accept that self-reported health-related QoL potentially differs from proxy assessment (43). The CDLQI, which was used in the present population, is the most widely used instrument for measuring skin-related QoL in children (20).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Lowe (41) noticed that one of the most important predictors of parental satisfaction in pediatric laceration repair is "provider performance, " comprising communication, attitude, hygiene and confidence of the physician. Many studies naturally address the parental point of view, (41,42) as self-reports are limited by age, but thus accept that self-reported health-related QoL potentially differs from proxy assessment (43). The CDLQI, which was used in the present population, is the most widely used instrument for measuring skin-related QoL in children (20).…”
Section: Quality Of Lifementioning
confidence: 99%
“…This derivative has a longer side chain and forms a stronger and more flexible bond, with a three-dimensional breaking strength four times that of butyl-2-cyanoacrylate 6,12 . Several investigations into the cosmetic results of wound closure have been published in the last few years, but most were performed in children 4,8,18 , with the results difficult to transfer to facial wounds in adults, and in many studies the wounds were not standardized for length, localization and shape 11,22 . The results also conflict with regard to the cosmetic results of wound closure with adhesives as opposed to sutures; whereas some authors reported superior results for wound closure with sutures 1,21 , other studies demonstrated better or equal cosmetic results with cyanoacrylates 8,22 .…”
mentioning
confidence: 99%
“…( J AAPOS 2012;16: 168-172) I n previous studies authors have documented the benefits of wound closure with tissue adhesives compared with sutured wound closure. [1][2][3][4][5][6][7] The purpose of this report is to describe cases of periorbital cellulitis after wound closure of traumatic periorbital lacerations with 2-octyl cyanoacrylate (Dermabond; Ethicon, Inc, Somerville, NJ) and to evaluate the existing literature to identify a trend toward an increased infection rate with tissue adhesive closure.…”
Section: Discussionmentioning
confidence: 99%